Analysis of the Impact of Fiscal Incentives on the Development of Electric Vehicles in Indonesia's Green Economy Transition (2020-2024) - Puspita, Dyah Hanum; Meshanayagi, Salsabila Raisha; Fadhlirobby, Faiz; Pasya, Revaya Rizqia; Pertiwi, Elyana Ade (Jurnal sosial dan sains, 2025)
Accelerating the transition to a green economy is the main demand for developing countries such as Indonesia amid the increasing impact of climate change. This study analyzes the effectiveness of fiscal incentive policies regulated in Presidential Regulation No. 79 of 2023 on increasing the use of battery-based electric vehicles as part of the national clean energy strategy. The study was conducted using a quantitative descriptive approach with secondary data from the Central Statistics Agency, the Ministry of Energy and Mineral Resources, and the 2021–2030 Rencana Usaha Penyediaan Tenaga Listrik (RUPTL). The (PCA) method is used to assess sectoral contributions to variations in carbon emissions, while the ANOVA test is applied to identify significant differences between years. The results of the analysis show that there is a surge in the adoption of electric vehicles after the policy is implemented, but CO₂ emissions still fluctuate highly, especially in the industrial and electricity sectors. The highest score of the first key component (PC1) in 2021 indicates a pivotal point in the changing sectoral dynamics towards green transformation, but the misalignment in the following years highlights the need for cross-policy integration. Thus, the effectiveness of fiscal incentives is not enough to rely solely on the demand for electric vehicles but also requires energy system reform and the readiness of economic structures to adopt low-emission technologies.